Intrinsic quantized anomalous Hall effect in a moiré heterostructure - Serlin, M.; Tschirhart, C. L.; Polshyn, H.; Zhang, Y.; Zhu, J.; Watanabe, K.; Taniguchi, T.; Balents, L.; Young, A. F. (Science (American Association for the Advancement of Science), 2020)
Quantum anomalous Hall effect—the appearance of quantized Hall conductance at zero magnetic field—has been observed in thin films of the topological insulator Bi 2 Se 3 doped with magnetic atoms. The doping, however, introduces inhomogeneity, reducing the temperature at which the effect occurs. Two groups have now observed quantum anomalous Hall effect in intrinsically magnetic materials (see the Perspective by Wakefield and Checkelsky). Serlin et al. did so in twisted bilayer graphene aligned to hexagonal boron nitride, where the effect enabled the switching of magnetization with tiny currents. In a complementary work, Deng et al. observed quantum anomalous Hall effect in the antiferromagnetic layered topological insulator MnBi 2 Te 4 . Science , this issue p. 900 , p. 895 ; see also p. 848 Transport measurements indicate quantized Hall conductance without a magnetic field. The quantum anomalous Hall (QAH) effect combines topology and magnetism to produce precisely quantized Hall resistance at zero magnetic field. We report the observation of a QAH effect in twisted bilayer graphene aligned to hexagonal boron nitride. The effect is driven by intrinsic strong interactions, which polarize the electrons into a single spin- and valley-resolved moiré miniband with Chern number C = 1. In contrast to magnetically doped systems, the measured transport energy gap is larger than the Curie temperature for magnetic ordering, and quantization to within 0.1% of the von Klitzing constant persists to temperatures of several kelvin at zero magnetic field. Electrical currents as small as 1 nanoampere controllably switch the magnetic order between states of opposite polarization, forming an electrically rewritable magnetic memory.